THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN STRENGTHENING STUDENTS' SELF-CONTROL - Citra Puspita Maulida; Kasuwi Saiban; Umi Salamah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2026)
Seeing the current phenomenon, various problems often arise due to a  person's lack of self-control. In the process of strengthening students' self-control,  teachers have an important role, especially Islamic Religious Education teachers.  The purpose of this study is to describe the role of Islamic Religious Education  teachers in strengthening self-control aspects of behavioral control, cognitive  control, and decisional control of students. This study uses a qualitative approach  with a descriptive research type. Data collection: interviews, observation, and  documentation. Data checking uses triangulation, the "Miles Huberman and  Saldana" model, namely data condensation, data presentation, and drawing  conclusions. The implications of strengthening studens self control include  developing their Islamic caracter, improving the quality of learning, and achieving  the goals of Islamic educations. Integrating self control into Islamic education is  not only key to academic success but also fosters a strong Islamic character.  Research results: 1) Carrying out religious activities in schools includes: a  program of reciting the Koran before learning for 1 hour, congregational dhuhur  prayer, istighotsah, congregational dhuha prayer, infaq on Friday, clean Friday,  healthy Friday, shaking hands with teachers before entering school,  commemoration of Islamic holidays, and Islamic Religious Education teachers  explain the material by connecting examples in everyday life. 2) Providing a point  book system for students who violate school rules, if there are a lot of points then  there will be a call from the parents, giving educational sanctions to students who  violate the rules, and teachers providing good examples. 3) Involving students in  routine religious activities at school, implementing discussion or group methods  to make it easier for students to solve learning problems, Islamic Religious  Education learning has a question and answer session if there is material that is  not yet understood, providing guidance and counseling facilities to help solve  student problems, as well as good cooperation between several parties concerned. This study gives the impression that the role of Islamic Religious Education teachers in religious training and role models is able to strengthen students' self-control, thereby helping students to be more disciplined, able to control their behavior, think more positively, and be wiser in making decisions in the school environment and in everyday life.